Transnational Space and Homosexuality: An Ethnographic Analysis of Same-sex Intimate Cross-border Relationships Among Men in Haiti and their Migrant Partners Across the Haitian Diaspora - Charles, Carlo Handy (My University, 2023)
Since the 1950s, Haitian transnational migrants have ensured the socioeconomic survival of many nonmigrants in Haiti by sending billions of US dollars annually to their families and friends back home. While Haitian migrants are often perceived as having a positive economic impact on Haiti, some are criticized for engaging in homosexual behaviours, seemingly infringing on ‘traditional’ Haitian family values in a largely conservative ‘Christian’ society. This revives old debates about migrants’ role in using their money to normalize same-sex identity and practices and pervert sexual morality and ‘acceptable’ gender norms among nonmigrants in Haiti. Accordingly, men in Haiti are involved in same-sex intimate transnational relationships with migrants from the Haitian diaspora because of their precarious socioeconomic status in Haiti and not necessarily because they may be gay. Although homosexuality has always existed in Haiti and same-sex intimate relationships among men in Haiti and those abroad have long existed, these relationships have rarely been studied in the literature on transnational migration and sexualities. To fill this gap, this thesis draws on eleven months of ethnographic fieldwork and forty-four semi-structured interviews with men in Northern Haiti to show how homosexuality intersects with transnational space and socioeconomic inequality to shape and organize transnational processes and same-sex intimate relationships involving men in Haiti and their migrant partners across the Haitian diaspora in the United States, Canada, France, Brazil, Chile, and the Dominican Republic.
Keywords: Migration; Transnationalism; Haiti; Homosexuality; Inequality; Remittances; Intimacy; Mobility